Balneolotherapy Features of Natural Thermal Source from Pertek (Turkey-Tunceli) Due to Its Some Chemical, Radioctivity and Biological Parameters - Erecevit Sönmez , Pinar (Progress in Nutrition, 2022)
It can also be defined as a discipline that reviews the factors of balneology or hydrotherapy, which are alternative treatment methods for public health, from chemical, biological and medical aspects. In this study, it was aimed to investigate whether the underground waters in the Pertek district of Tunceli province are suitable for balneology. Chemical, radioactivity analysis, microbiological quality, antimicrobial activities were determined in relation to natural groundwater and its ability to be a natural healing source was investigated. When the chemical content is examined, it was determined to be bromide amount is 0.24 mg / L, Iodine (I); 1.9 mg / L, sulfur (S); 0.02 mg / L, boron (B): 2676 µg / L, silicium (Si); 1.9 mg / L. With respect to the results, thermal water has the feature to be used in balneolotherapy. According to the results of the radioactivity analysis, alpha (α) is 0.15 Bq / L; Beta (β) is <0.30 Bq / L and radon (Rn) is <13.4 Bq / L tritium (T) content is <10 Bq / L (<83.33 TB) and it is included in both mineral and young water group. This ground water and they comply with the standards in terms of microbiology (Total bacteria, coliform, Escherichia coli). Its antibacterial, antifungal and antidermatophyte properties prove to be a healing source. We confirmed the effectiveness of this healing water to both protect and promote human health and also reach the newest and most effective treatment modalities by using related water in Health and Thermal Tourism.